The influence of leadership styles on job stress and turnover intention in the insurance industry in jaffna district - Raveendran, T. (University of Jaffna, 2016)
Leader's leadership type is the critical factor for the success of the organization. This research explores the relationships among leader's leadership style, subordinate's personality characteristic, and job stress and turnover intention in the insurance industry in Jaffna District. Simple random sampling method was used to collect data. A total of 235 questionnaires were sent, of which 176 returned questionnaires are valid. The conclusions drawn from this study are (1) Leadership style has significant impact on job stress; (2) Leadership style has significant impact on turnover intention; (3) Job stress is positively associated with turnover intention; (4) Personality characteristic has no moderating effect on the relationship between leadership style and job stress; (5) Personality characteristic brings no moderating effect on the relationship between job related stress and turnover intention; (6) Job stress has mediation effect on the association between leadership style and turnover intention.
Keywords: Leadership style; Job stress; Personality characteristic; Turnover intention